Long-Term Obeticholic Acid Therapy Improves Histological Endpoints in Patients With Primary Biliary Cholangitis - Bowlus, Christopher L.; Pockros, Paul J.; Kremer, Andreas; Parés, Albert; Forman, Lisa M.; Drenth, Joost P.H.; Ryder, Stephen D.; Terracciano, Luigi; Jin, Yuying; Liberman, Alexander; Pencek, Richard; Iloeje, Uche; et al. (Clinical Gastroenterology and Hepatology, 2020)
Background & Aims: Primary biliary cholangitis (PBC) is an autoimmune disease characterized by bile duct destruction that can progress to cirrhosis. A liver biopsy substudy was conducted in the PBC obeticholic acid (OCA) International Study of Efficacy (POISE) to determine the long-term effects of OCA on liver damage and fibrosis in patients with PBC. POISE is a phase 3, double-blind, placebo-controlled, randomized trial with a 5-year open-label extension that evaluated 5 to 10 mg OCA daily in patients who were intolerant or unresponsive to ursodeoxycholic acid. Methods: Liver biopsy specimens were collected from 17 patients at time of enrollment in the double-blind phase and after 3 years of OCA treatment. Histologic evaluations were performed by 2 pathologists in a blinded, randomized fashion to determine the effects of OCA on fibrosis and other histologic parameters. Collagen morphometry assessments were performed by automated second harmonic generation and 2-photon excitation microscopy to observe quantitative measures of fibrosis. Results: From the time of enrollment until 3 years of treatment, most patients had improvements or stabilization in fibrosis (71%), bile duct loss (76%), ductopenia (82%), ductular reaction (82%), interface hepatitis (100%), and lobular hepatitis (94%). Over the 3-year period, we found significant reductions in collagen area ratio (median, –2.1; first quartile, –4.6, third quartile, –0.3; P =.013), collagen fiber density (median, –0.8; first quartile, –2.5; third quartile, 0; P =.021), collagen reticulation index (median, –0.1; first quartile, –0.3; third quartile, 0; P =.008), and fibrosis composite score (median, –1.0; first quartile, –2.5; third quartile, –0.5; P =.002). Conclusions: A subanalysis of data from the POISE study showed that long-term OCA treatment in patients with PBC is associated with improvements or stabilization of disease features, including ductular injury, fibrosis, and collagen morphometry features (ClinicalTrials.gov no: NCT01473524 and EudraCT no: 2011-004728-36).
CRIS-Team Scopus Importer:2020-03-27
Keywords: Farnesoid X Receptor Agonist; FXR Agonist; Hepatic; Liver Disease